Evidence for magma mixing during Triassic magmatism in West Qinling, China: Constraints from petrology, geochemistry, U–Pb zircon geochronology, and Sr–Nd–Hf isotopic of the Baguashan pluton. (17th August 2021) - Li, Xuefeng; Dong, Guochen; Yu, Xiaofei; Li, Yongsheng; Santosh, M.; Lv, Xin; Xia, Qing
Abstract : The West Qinling Orogen, which forms the western part of the Qinling Orogenic Belt, is characterized by the voluminous distribution of Triassic granitoids. Here, we investigate the Baguashan monzogranite which hosts numerous mafic microgranular enclaves (MMEs). We present zircon U–Pb–Hf and whole‐rock geochemical as well as Sr–Nd isotopic data of the monzogranites and MMEs with a view to gain insights on the petrogenesis and geodynamic setting. Zircon LA‐ICP‐MS U–Pb dating yields ages of 219.0 ± 1.7 Ma and 219.5 ± 1.6 Ma for the MMEs, and 214.2 ± 1.3 Ma for the host monzogranite, suggesting formation from coeval magmas. The host monzogranites show high SiO2, Rb, Ba, and Th contents, but low TiO2, MgO, P2 O5 values, with A/CNK of <1.1. Zircon grains from monzogranites show ε Hf ( t ) values in the range of −6.3 to +3.2 with corresponding two‐stage Hf model ages ( T DM2 ) of 1.39–2.25 Ga. The MMEs are mostly elliptical or spherical in shape and have lower SiO2 and Th contents, but higher MgO, TiO2, and CaO, and ε Hf (t) values ranging from −6.1 to +5.7 with TDM2 of 1.17–2.23 Ga. The Sr–Nd isotopic data for MMEs and monzogranites show ( 87 Sr/ 86 Sr)i ratios ranging from 0.7059 to 0.7069 and low ε Nd ( t ) values ranging from −6.07 to −4.18, suggesting a crustal origin. Based on the relatively homogeneous Sr–Nd–Hf isotopic compositions, we suggest that the MMEs represent magma mixing, and the mafic magma injected into the felsic magma chamber was probably derived by the reworking of mafic lower crust with a contribution of juvenile materials. We propose a model involving delamination of thickened lower crust below the West Qinling Orogen after the collision between the North China Block and the South China Block in the Late Triassic. Subsequently, the lower crust was partially melted by the heat input from the upwelling asthenosphere and produced the mafic magma. Partial melting of the ancient metamorphic rocks generated the granitic magma. The interaction of mafic and felsic magmas occurred within a post‐collisional tectonic setting in the Late Triassic. Abstract : The interaction of mafic and felsic magmas occurred within a post‐collisional tectonic setting and was related to the delamination of thickened lower crust in the Late Triassic.